Assessing the Dynamics of Dissolved Organic Matter (DOM) in the Coastal Environments Dominated by Mangroves, Indian Sundarbans - Sanyal, Prasun; Ray, Raghab; Paul, Madhusudan; Gupta, Vandana Kumari; Acharya, Avanti; Bakshi, Sneha; Jana, Tapan Kumar; Mukhopadhyay, Sandip Kumar (Frontiers in Earth Science, 2020)
Tidal transport from coastal wetlands (“outwelling”) together with riverine fluxes provide most important sources of terrigenous organic matter (OM) to the ocean. The flux of dissolved organic carbon (DOC) from the mangrove swamps accounts for 10% of the terrestrial DOC flux to the coastal water. This study examines the sources, distribution, and export of dissolved OM at inter-annual, seasonal and diurnal basis along the estuaries located at the Sundarbans, world’s largest deltaic mangrove and heritage site. Sampling was carried out from riverine (Hooghly) and mangrove-dominated tidal estuaries (Saptamukhi, Thakuran, Matla) covering all three seasons (pre-monsoon, monsoon and post-monsoon) during 2012-2017. DOC varied at a broad range from 109 to 462 µM (n = 146) with higher concentration observed in the Hooghly (383±120 µM, n = 35) than the mangrove estuaries (246±82 to 266±120 µM, n = 111). Nonconservative mixing of DOC along the salinity gradient attested to mangrove input, particularly in the polyhaline waters. Upper and mid estuarine zones of the mangrove estuaries showed slightly higher DOC concentration (270±92 µM, n = 84, salinity range 18-25) than the mouth (250±85 µM, n = 27, salinity range 26-27) because of the dilution with marine waters having low DOC concentration and shorter water residence time downstream. Seasonally, higher DOC concentration during the post-monsoon might be linked to higher litterfall promoting leaching of organic compounds to the water. In that connection, colored dissolved organic matter (CDOM) could be the by-product of mangrove litter leaching, and its absorption coefficient (at 350 nm) exhibited non conservative mixing pattern at wide ranges from 2.5 to 7.6 m-1 (n = 40). CDOM enrichment was observed in the surface water during the low tide when outwelling maximized. Overall, central and eastern part of the Indian Sundarbans showed enrichment of more terrigenous type CDOM (evident from optical proxies e.g. S275-295 and SUVA254) than the western part, probably due to greater mangrove productivity in the eastern side. Flux estimates of DOM resulted in higher yield and export of mangrove-derived DOC but lower export of CDOM to the Bay of Bengal as compared to their riverine transport.